Ordering Illegal Migration Terminology: the Migration Legality Cube - Wojciech Janicki (Barometr Regionalny, 2018)
In the subject literature, the terms “illegal migration” and “illegal migrant” encompass many categories of processes, people, and phenomena that have little to do with migration as a movement of people in space. This includes, most prominently, unauthorized employment and unauthorized residence in the receiving country. Both of these circumstances may be related to prior illegal migration, but do not necessarily have to be. The physical process of migration may have taken place entirely in accordance with the law. This is the starting point for the reconsideration of the standard migration terminology, as proposed in this paper. As three basic dimensions of illegality associated to date with migration analysis may focus on one person in as many as eight different combinations, this would require us to describe a single person using three different terms, which would quickly turn out to be inefficient. For practical reasons, the most convenient term is illegal migrant. Given its vague nature, however, the paper proposes to supplement this using the classification presented in the Migration Legality Cube encompassing eight types, depending on which group of migrants is in focus. This will make it easier for analysts and laymen alike to find their way in the ocean of uncertainty in which current debates on migration drift — and often founder.